The Effect of Gamification Approach and Teams Games Tournament in Term of Learning Interest on Students’ Understanding of Mathematical Concepts - Wulandari, Hesti; Amaliyah, Nurrohmatul (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Understanding mathematical concepts in mathematics learning is a crucial skill that students must possess to support the smooth running of teaching and learning activities. Pre-research results at an elementary school in East Jakarta indicate that students' understanding of mathematical concepts is still relatively low, as reflected in their suboptimal daily test scores. Therefore, researchers are interested to use a learning approach that can improve students' mathematical reasoning ability, namely the Gamification and Teams Games Tournament (TGT) learning approach in terms of learning interest with the aim of knowing: 1) the effect of gamification and TGT approaches on students' understanding of mathematical concepts; 2) the effect of learning interest on students' understanding of mathematical concepts; 3) the interaction between gamification and TGT approaches and students' learning interest. This study was a Quasy Experimental study with a 2-design factorial. The population and sample in this study were all students of class V at one of the elementary schools in East Jakarta, the control class is VA grade and the experimental class is VB grade. Data from questionnaires and understanding of mathematical concepts were analyzed using twoway ANOVA. Based on data analysis, the following results were found: (1) there is the effect of gamification and TGT approaches on students' understanding of mathematical concepts; (2) there is an effect of learning interest on students' understanding of mathematical concepts; and (3) there is an interaction between gamification and TGT approaches and students' learning interests. The results of the study showed that the gamification approach was more effective than the TGT model in improving students' understanding of mathematical concepts, especially for students with high learning interests. Therefore, teachers are advised to apply the gamification approach as an innovative learning strategy that can accommodate differences in students' learning interests in the classroom. Abstrak Pemahaman konsep matematis dalam pembelajaran matematika merupakan kemampuan penting yang harus dimiliki peserta didik untuk mendukung kelancaran kegiatan belajar mengajar. Hasil pra-penelitian di sebuah SD di wilayah Jakarta Timur menunjukkan bahwa tingkat pemahaman peserta didik terhadap konsep matematis masih tergolong rendah, yang tercermin dari nilai ulangan harian yang belum optimal. Oleh karena itu, peneliti terdorong untuk menggunakan pendekatan pembelajaran yang dapat meningkatkan kemampuan penalaran matematis peserta didik, yaitu pendekatan pembelajaran Gamifikasi dan Teams Games Turnament (TGT) ditinjau dari minat belajar dengan tujuan untuk mengetahui: 1) pengaruh pendekatan gamifikasi dan TGT terhadap pemahaman konsep matematis peserta didik; 2) pengaruh minat belajar terhadap pemahaman konsep matematis peserta didik; 3) interaksi antara pendekatan gamifikasi dan TGT dengan minat belajar peserta didik. Penelitian ini merupakan penelitian Quasy Eksperimental dengan desain 2 faktorial. Populasi dan sampel dalam penelitian ini yaitu seluruh peserta didik kelas V di salah satu sekolah dasar di Jakarta Timur, sebagai kelas kontrol yaitu kelas VA dan sebagai kelas eksperimen yaitu kelas VB. Data hasil angket dan pemahaman konsep matematis dianalisis menggunakan uji anava 2 jalur. Berdasarkan analisis data, ditemukan hasil-hasil sebagai berikut: (1) terdapat pengaruh pendekatan gamifikasi dan TGT terhadap pemahaman konsep matematis peserta didik; (2) terdapat pengaruh minat belajar terhadap pemahaman konsep matematis peserta didik; dan (3) terdapat interaksi antara pendekatan gamifikasi dan TGT dengan minat belajar peserta didik. Hasil penelitian menunjukkan bahwa pendekatan gamifikasi lebih efektif daripada model TGT dalam meningkatkan pemahaman konsep matematis peserta didik, terutama bagi peserta didik dengan minat belajar tinggi. Oleh karena itu, guru disarankan untuk menerapkan pendekatan gamifikasi sebagai strategi pembelajaran inovatif yang mampu mengakomodasi perbedaan minat belajar peserta didik di kelas.